Checklist of mammals from Mato Grosso do Sul, Brazil - Tomas,Walfrido Moraes (2017)
Abstract We updated the checklist of mammals from Mato Grosso do Sul, Brazil based on primary records only. One hundred and sixty-six mammal species were listed as occurring in the state, 47 of them being medium to large, 47 small mammal and 73 bat species. The listed species are distributed in 31 families: Didelphidae (17 spp.), Dasypodidae (7 spp.), Myrmecophagidae (2 spp.), Cebidae (1 sp.), Callithrichidae (2 spp.), Aotidae (1 sp.), Pitheciidae (1 sp.), Atelidae (1 sp.), Leporidae (1 sp.), Felidae (7 spp.), Canidae (4 spp.), Mustelidae (5 spp.), Mephitidae (2 spp.), Procyonidae (2 spp.), Tapiridae (1 sp.), Tayassuidae (2 spp.), Cervidae (4 spp.), Sciuridae (1 sp.), Cricetidae (22 spp.), Erethizontidae (1 sp.), Caviidae (3 spp.), Dasyproctidae (1 sp.), Cuniculidae (1 sp.), Echimyidae (4 spp.), Phyllostomidae (41 spp.), Emballonuridae (2 spp.), Molossidae (16 spp.), Vespertilionidae (9 spp.), Mormoopidae (1 sp.), Noctilionidae (2 spp.), and Natalidade (1 sp.). These numbers represent an increase of fourteen species with primary records for the state in comparison with the previously published checklist. However, it is evident the scarcity of information at several regions of the state, and the need of implementation of regional zoological collections. The state of Mato Grosso do Sul represent only 4.19% of the Brazilian territory, but the number of mammal species reach 24.13% of the known species occurring in the country.